Cover Feature: Versatile Bispidine‐Based Bifunctional Chelators for 64CuII‐Labelling of Biomolecules (Chem. Eur. J. 9/2020). Issue 9 (21st January 2020) - Singh, Garima; Zarschler, Kristof; Hunoldt, Sebastian; Martínez, Irma Ivette Santana; Ruehl, Carmen L.; Matterna, Madlen; Bergmann, Ralf; Máthé, Domokos; Hegedüs, Nikolett; Bachmann, Michael; Comba, Peter; Stephan, Holger
Abstract : Bifunctional chelators for targeted nuclear imaging have been developed on the basis of bispidines. Reductive alkylation at the relatively inert C9‐position of bispidols paves the way for generating a number of derivatives ready to be coupled to a variety of targeting vector molecules. As these bispidine derivatives form highly stable complexes with the positron emitter 64 Cu II, they are virtually predestined for their application in the field of diagnostic positron emission tomography (PET). More information can be found in the Full Paper by K. Zarschler, P. Comba, H. Stephan, et al. on page 1989 .